Moslem Wear Terinspirasi dari Motif Tabuik - Maysharah, Maysharah; Rahmanita, Nofi; Imelda, Desra; Fatrina, Novina Yeni (Style : Journal of Fashion Design, 2024)
Tabuik is an annual celebration carried out by the pariaman people of west Sumatra, the tabuik ceremony anchors tabuik to the sea. There are many parts that have meaning, namely there are salapan flowers have eight (8) petals, four on the top and four on the bottom. Tabuik is a collaboration of custom and religion, so the meaning of the salapan flower is that the four petals symbolize religion. While the biliak-biliak tabuik are seveb rooms dedicated to niniak mamak, religious scholars, cadiak clever, community leaders, urang sumando, children and kamanakan. Then the seven are the components of society at the time. The concept of creating this work takes the form of salute flowers and biliaks in muskim wear clothing is clothing that is closed and loose, the process of embodiment of this work begins with exploration to produce sketches and designs, then after that the artist carriest out the process of embodiment by sewing the work. The resulting work which means it has space or can be filled by the user’s body. The color that is applied to the work is the color of the moodboard